The Dopamine Assisted Synthesis of MoO3/Carbon Electrodes With Enhanced Capacitance in Aqueous Electrolyte - Norouzi, Nazgol; Omo-Lamai, Darrell; Alimohammadi, Farbod; Averianov, Timofey; Kuang, Jason; Yan, Shan; Wang, Lei; Stavitski, Eli; Leshchev, Denis; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.; et al. (Frontiers in Chemistry, 2022)
A capacitance increase phenomenon is observed for MoO3 electrodes synthesized via a sol-gel process in the presence of dopamine hydrochloride (Dopa∙HCl) as compared to α-MoO3 electrodes in 5M ZnCl2 aqueous electrolyte. The synthesis approach is based on a hydrogen peroxide-initiated sol-gel reaction to which the Dopa∙HCl is added. The powder precursor, (Dopa)xMoOy, is isolated from the metastable gel using freeze-drying. Hydrothermal treatment (HT) of the precursor results in the formation of MoO3 accompanied by carbonization of the organic molecules; designated as HT-MoO3/C. HT of the precipitate formed in the absence of dopamine in the reaction produced α-MoO3, which was used as a reference material in this study (α-MoO3-ref). Scanning electron microscopy (SEM) images show a nanobelt morphology for both HT-MoO3/C and α-MoO3-ref powders, but with distinct differences in the shape of the nanobelts. The presence of carbonaceous content in the structure of HT-MoO3/C is confirmed by FTIR and Raman spectroscopy measurements. X-ray diffraction (XRD) and Rietveld refinement analysis demonstrate the presence of α-MoO3 and h-MoO3 phases in the structure of HT-MoO3/C. The increased specific capacitance delivered by the HT-MoO3/C electrode as compared to the α-MoO3-ref electrode in 5M ZnCl2 electrolyte in a -0.25 – 0.70 V vs Ag/AgCl potential window triggered a more detailed study in an expanded potential window. In the 5M ZnCl2 electrolyte at a scan rate of 2 mV s−1, the HT-MoO3/C electrode shows a second cycle capacitance of 347.6 F g−1. The higher electrochemical performance of the HT-MoO3/C electrode can be attributed to the presence of carbon in its structure, which can facilitate electron transport. Our study provides a new route for further development of metal oxides for energy storage applications.